Microcontroller (M68HC11) for fluid flow control - Adam, Nor Arina (2006)
Process control becomes one of the important elements in industry and chemical laboratory. The purpose of this project is to control fluid flow by using microcontroller (M68HC11) and other component such as solenoid valve, keypad and level detector. When entering value of liquid by using keypad, user can get the amount needed correctly. The opening and closing of the solenoid valve depending on the programming design. By using automatic control, it will prevent overflow occur to the system and suitable for industry and chemical laboratory where accuracy of liquid needed is critical. In daily life, microcontroller has made an invaluable contribution to electronics and logic design everywhere. On the other hand, their flexible and programmable natures have led us to embrace embedded functionality in every aspect of our worldly interactions. The implementation of the usage of microcontroller in controlling fluid flow would be an advantage in process control system. The integration between each part of hardware will determine the successfulness of this project.